Habitat-mediated dive behavior in free-ranging grey seals. - Mark Jessopp (Public Library of Science (PLoS), 2013)
Understanding the links between foraging behaviour and habitat use of key species is essential to addressing fundamental questions about trophic interactions and ecosystem functioning. Eight female grey seals (Halichoerus grypus) were equipped with time-depth recorders linked to Fastloc GPS tags following the annual moult in southwest Ireland. Individual dives were coupled with environmental correlates to investigate the habitat use and dive behaviour of free-ranging seals. Dives were characterised as either pelagic, benthic, or shallow (where errors in location and charted water depth made differentiating between pelagic and benthic dives unreliable). Sixty-nine percent of dives occurring in water >50 m were benthic. Pelagic dives were more common at night than during the day. Seals performed more pelagic dives over fine sediments (mud/sand), and more benthic dives when foraging over more three-dimensionally complex rock substrates. We used Markov chain analysis to determine the probability of transiting between dive states. A low probability of repeat pelagic dives suggests that pelagic prey were encountered en route to the seabed. This approach could be applied to make more accurate predictions of habitat use in data-poor areas, and investigate contentious issues such as resource overlap and competition between top predators and fisheries, essential for the effective conservation of these key marine species.